ANALISIS PERPINDAHAN MEREK: Studi Kasus Pengguna Smartphone Oppo Di Ciganjur, Jagakarsa - Endah Mahayu Putri, - (2019)
This research is a quantitative research that aims to determine the effect of product attributes, variety seeking, and prices on brand switching. The population in this study were Oppo smartphone users in Ciganjur, Jagakarsa. The sample size was taken as many as 75 respondents, with a non probability sampling method with a purposive sampling method. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis with SmartPLS 3.2.7 software. The results of this study indicate that (1) Product attributes have a positive and significant influence on brand switching. (2) variety seeking has no influence and is not significant to brand switching (3) Price has a positive and significant influence on brand switching. Of the three independent variables namely product attributes, looking for variations and prices that provide the largest contribution is the product attribute variable.